„I widział Bóg, że światło było dobre...” (Rdz 1,4). Motyw światła w kapłańskim opowiadaniu o stworzeniu (Rdz 1,1-2,4a) - Napora, Krzysztof; Lakhmitskaya, Tatsiana (Verbum Vitae, 2016)
In our analysis we attempt to demonstrate the exceptional character of light within the act of creation. This uniqueness, in our view, can be demonstrated to be the background to the structure of the entire Priestly Creation Narrative, as well as the particular focus of Gen 1,3-5. In the theological perspective of the priestly redactor, light stands out clearly from God’s other creative acts, its significance extending far beyond its obvious physical properties. The creation of light not only sets in motion the cosmic clock but it also initiates space-time, in which all the subsequent acts of creation take place. The creation of light makes the order of creation feasible and indeed determines it. Its appearance seems to accompany the theophany of God, thus it constitutes a key element of God’s dominion over the forces of chaos.